Prevalence and clinical significance of antibodies to ribonucleoproteins in systemic lupus erythematosus in Malaysia. - Wang, C.L.; Ooi, L.; Wang, F. (1996)
One hundred and seventy patients with systemic lupus erythematosus (SLE) were studied for the prevalence of antibodies to the small RNA-associated proteins Ro/SSA, La/SSB, Sm, U1RNP and Sm. The relationship of these autoantibodies to different races, sexes and clinical manifestations of SLE was evaluated. Passive immunodiffusion was employed using human spleen extract as antigen source for Ro and rabbit thymus extract for La, Sm and U1RNP. We found the prevalence of antibodies to be as follows: anti-Ro/SSA, 36%; anti-La/SSB, 8%; anti-Sm, 15% ; anti-U1RNP, 21%. Except for a low prevalence of anti-La, the prevalence of these antibodies was similar to that in Western studies, The prevalence of anti-Ro/SSA is similar to that reported in the Western studies, but lower than that reported in the Oriental patients from Singapore and Hong Kong. Linkages of anti-Ro with anti-La antibodies were usual; however, although anti-Sm antibodies were usually associated with anti-U1RNP, they were more frequently associated with anti-Ro antibodies. The Malay patients had a high prevalence of anti U1RNP compared to other races. No gender difference was detected. Anti-Sm antibody was associated with serositis and anti-U1RNP antibodies with Raynaud's phenomenon. No association was found between the presence of skin renal or cerebral manifestations and any specific antibodies or combination of antibodies.